2015
DOI: 10.1080/15381501.2013.806235
|View full text |Cite
|
Sign up to set email alerts
|

Identifying HIV-Infected Women's Psychosocial Stressors: Findings from a Qualitative Study

Abstract: To inform future psychosocial interventions for HIV-infected women, five focus groups were conducted with 29 HIV-infected women (72% African-American). Sessions were audio-recorded, transcribed, and coded by two raters. HIV-specific stressors included difficulties with serostatus disclosure, HIV medication adherence, and HIV-related discrimination. Stressors not directly linked to HIV were described as more concerning and included mental health or substance use problems, relationship challenges, caretaking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, they may be afraid of telling others of serostatus due to the fear of potential negative consequences following disclosure such as condemn, isolation, or anger from family or friends [44]. Challenges surrounding HIV serostatus disclosure (i.e., whether disclose serostatus to others, who to disclose, when to disclose, and how to disclose) have been described being particularly stressful to most PLWH in many other studies [17][18][19]. Previous studies also reported that the lack of communicating skills about this sensitive topic can be the barrier to appropriate disclosure [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may be afraid of telling others of serostatus due to the fear of potential negative consequences following disclosure such as condemn, isolation, or anger from family or friends [44]. Challenges surrounding HIV serostatus disclosure (i.e., whether disclose serostatus to others, who to disclose, when to disclose, and how to disclose) have been described being particularly stressful to most PLWH in many other studies [17][18][19]. Previous studies also reported that the lack of communicating skills about this sensitive topic can be the barrier to appropriate disclosure [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers have noticed the limitation of using general life events scales to assess stress among HIV population and have focused on the HIV-specific stress, most of them used qualitative method and were cross-sectional in design [17][18][19][20][21]. A quantitative assessment of stress among PLWH using a disease-specific stress instrument with established validity and reliability is required to elucidate the impact of HIV infection on PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, stigma and discrimination are reported among WLWH more frequently than in men living with HIV, and may contribute to the lack of or delay to HIV testing among women . Women may especially fear disclosure if found to be HIV positive, more so if they come from communities with significant gender power inequities; they may have fears about HIV in general and choose not to be tested .…”
Section: Resultsmentioning
confidence: 99%
“…Disclosure of serostatus to children is one of the main concerns and psychological stressors of all mothers with HIV disease. 77,78 In a systematic review of disclosure to children younger than 12 years of age, Krauss et al found there were health (e.g., adherence, HIV testing of children, quality of life) and planning benefits (e.g., life planning, future care for children) for both HIV-positive and HIV-negative children with caregiver disclosure. 79 Other challenges AYA with chronic disease often face challenges transitioning from pediatric or adolescent to adult-centered medical care.…”
Section: Postnatal Period and Beyondmentioning
confidence: 99%